PENGARUH WORK LIFE BALANCE DAN BEBAN KERJA TERHADAP KINERJA KARYAWAN WANITA DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL MEDIASI PADA DINAS SOSIAL PEMBERDAYAAN PEREMPUAN DAN PERLINDUNGAN ANAK KABUPATEN TANAH DATAR - Bulqis, Bulqis; Putri, Eka Risma (Gapenas Publisher, 2025)
This study aims to determine the effect of work-life balance and workload on the performance of female employees with organizational commitment as a mediating variable at the Social Service for Women's Empowerment and Child Protection of Tanah Datar Regency. The objects of this study were all 30 female employees of the Social Service for Women's Empowerment and Child Protection of Tanah Datar Regency. This type of research is quantitative research. The data collection method used a questionnaire. Data processing in this study used the SmartPLS 3 Analysis tool, and was analyzed using Partial Least Square (PLS) analysis. The analysis used in this study includes outer model analysis, inner model analysis and hypothesis testing. In this study, the results obtained Work-life balance has a positive and significant effect on the performance of female employees, Workload has a positive and significant effect on the performance of female employees, Organizational Commitment has a negative and insignificant effect on the performance of female employees, Work-life balance has a negative and insignificant effect on organizational commitment, Workload has a positive and significant effect on organizational commitment, Organizational commitment does not mediate the relationship between work-life balance and the performance of female employees, Organizational commitment does not mediate the relationship between work-life balance and the performance of female employees.